(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The objective of the study was to find out the comparison of occupational stress among Physical Education Teachers working in Government and Private School of Northern Region of India for the purpose of this study 600 physical education teachers were selected from different parts of the northern region the subjects age range was of 20-40 years and 41-60 years Occupational Stress Index questionnaire developed by A.K. Srivastava and A.P. Singh will be used to collect the data